Optimized Overcurrent Relay Coordination in a Microgrid System - Swathika, Odiyur V.G.; Hemapala, Udayanga (Recent Advances in Computer Science and Communications, 2020)
Background: Microgrids are a conglomeration of loads and distributed generators at a distribution level network. Since this network is no longer a single source fed network, the typical protection strategies may not be deployed. Reconfiguration is a topology changing feature that is visible in microgrid. This is also another factor that is to be considered while protecting the microgrid setup. Objective: To develop an optimized overcurrent relay coordination scheme for microgrid networks. Methods: Inorder to devise suitable overcurrent protection scheme for microgrids, initially the normal and fault currents are captured for all topologies of the microgrid. For each topology, the optimized time multiplier settings of overcurrent relays are computed using Dual Simplex Algorithm. This aids in clearing the fault as fast as possible from the network. Results: A 21-bus microgrid system is considered and the optimized overcurrent relay coordination scheme is realized for the same. Conclusion: The proposed optimized overcurrent relay coordination was tested successfully on the 21-bus microgrid system. The proposed protection scheme was capable of identifying the optimized Time Multiplier Setting values of the overcurrent relays in the path of fault clearance. It is evident that the proposed scheme can be conveniently extended to larger networks.
Keywords: Overcurrent relay